1997
DOI: 10.1042/bj3270877
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arg-401 of cytosolic serine hydroxymethyltransferase in subunit assembly and interaction with the substrate carboxy group

Abstract: In an attempt to identify the arginine residue involved in binding of the carboxylate group of serine to mammalian serine hydroxymethyltransferase, a highly conserved Arg-401 was mutated to Ala by site-directed mutagenesis. The mutant enzyme had a characteristic visible absorbance at 425 nm indicative of the presence of bound pyridoxal 5'-phosphate as an internal aldimine with a lysine residue. However, it had only 0.003% of the catalytic activity of the wild-type enzyme. It was also unable to perform reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Similarly, it was shown in eSHMT that the conserved T226 plays an important role in converting geminal diamine into the external aldimine [17]. It was shown that R363 in eSHMT and the corresponding residue R401 in rSHMT were essential for binding of substrate carboxy group [18,19]. Mutation of the conserved H134, H147 and H150 in rSHMT established their roles in the maintenance of oligomeric structure, cofactor binding and proton abstraction respectively [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was shown in eSHMT that the conserved T226 plays an important role in converting geminal diamine into the external aldimine [17]. It was shown that R363 in eSHMT and the corresponding residue R401 in rSHMT were essential for binding of substrate carboxy group [18,19]. Mutation of the conserved H134, H147 and H150 in rSHMT established their roles in the maintenance of oligomeric structure, cofactor binding and proton abstraction respectively [20].…”
Section: Introductionmentioning
confidence: 99%
“…rSHMT (wild type) and D89N SHMT were overexpressed and purified as described previously [19]. Briefly, the purification procedure involved ammonium sulphate fractionation, CMSephadex chromatography followed by gel-filtration using a Sephacryl S-200 column.…”
Section: Purification Of Wild-type and D89n Shmtmentioning
confidence: 99%
“…These mutants had significantly lower specific activity. Mutants such as K256Q, K256R and R401A were inactive [7,10]. The residue(s) involved in H % -folate binding have not been clearly defined by site-directed mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the active-site lysine residue, Lys-229, in eSHMT participates in product expulsion [8]. An analysis of mutants led to the identification of Arg-363 in eSHMT [9] and Arg-401 in rSHMT [10] (residues equivalent to each other) as being involved in interacting with the α-carboxy group of serine.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular Interaction between the Guanido Group and the Carboxyl Group-Molecular interaction between the guanido group of arginine and the carboxyl group in the substrate or the active site residues of enzyme was reported to be crucially involved in the interaction between the substrate and the enzyme (31)(32)(33)(34)(35)(36). The ionized guanido group of arginine can form a planar structure due to the sp 2 configuration of guanido carbon atom, so that a stable planar ion pair can be generated by forming a coplanar structure between the guanido group and the negatively charged carboxyl group.…”
Section: Figure 3 Stereo View Of Mae2 In Complex With Malonate or Mamentioning
confidence: 99%